Triplet pregnancy with severe preeclampsia: appropriate management - Yanti, Linda; Surtiningsih, Surtiningsih; Nurhayati, Cicih (MEDISAINS, 2020)
Introduction: The case of preeclampsia and triplet pregnancy is likely to cause hypertension in uncontrolled pregnant women if they are not managed properly, which may harm both the mother and the fetus. References for the treatment of similar cases are still uncommon. Therefore, this case study provides an overview of midwifery care management on cases of triplet pregnancy and severe preeclampsia.Case presentation: A case of exacerbated triplet pregnancy with severe preeclampsia is described in a 36-year-old woman who was recently detected at the third-trimester visit at 31 weeks four days' pregnancy.Conclusion: Management of patients with triplet pregnancies and severe preeclampsia is to perform standard antenatal care, ultrasound examinations in each trimester, hospital care, as well as psychological assistance.